2012
DOI: 10.2340/16501977-0928
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral upper limb exercise therapy after stroke: A systematic review

Abstract: Unilateral and bilateral training are similarly effective. However, intervention success may depend on severity of upper limb paresis and time of intervention post-stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 74 publications
5
50
0
3
Order By: Relevance
“…Possible risks of bias, like blinding of assessors, did not seem to influence lack of difference between dose-matched trials and non-dose matched trials. These findings are in agreement with a recent trial(82) and meta-analysis(84) showing that dose-matched trials of mCIMT in which the control group received an equal dose of bilateral arm training failed to report significant differences in overall effect sizes. Despite the finding that (m)CIMT may increase short-term(50, 85) and long-term cortical activation patterns, (42, 50, 86), the underlying mechanisms responsible for improvements require further investigation.…”
Section: What Drives (M)cimt?supporting
confidence: 91%
“…Possible risks of bias, like blinding of assessors, did not seem to influence lack of difference between dose-matched trials and non-dose matched trials. These findings are in agreement with a recent trial(82) and meta-analysis(84) showing that dose-matched trials of mCIMT in which the control group received an equal dose of bilateral arm training failed to report significant differences in overall effect sizes. Despite the finding that (m)CIMT may increase short-term(50, 85) and long-term cortical activation patterns, (42, 50, 86), the underlying mechanisms responsible for improvements require further investigation.…”
Section: What Drives (M)cimt?supporting
confidence: 91%
“…BT of skills is shown to be present in stroke patients: it is possible that the repetitive training of a simple task performed by the healthy hand, "teaches" to the paretic hand the motor skill necessary to lower the time of execution of the NHPT. These findings can be useful for develop new rehabilitation strategies, in fact they are consistent with the recent growing evidence that the rehabilitation of the upper limb is based on principles of motor learning that include: (I) intense, active repetitive movement; (II) sensorimotor and proprioceptive integration, given the important role that sensory events play on motor learning in the normal and post-stroke states; (III) great importance of attention span and visual control given the effects that these have in normal and neurologically impaired brains [25][26][27][28][29].…”
Section: Discussion and Directions For Further Researchmentioning
confidence: 99%
“…Moreover a recent review article of van Delden et al [29] who performed a complete meta-analysis of many recent research protocols suggested that unilateral training is best suited for stroke survivors with mild to moderate upper limb hemiparesis. Therefore it is possible that BT will fail to improve the long term recovery of hand function in chronic stroke survivors.…”
Section: Limitationsmentioning
confidence: 99%
“…The variations are very much dependent on the specific conditions of individuals regarding the location and size of lesion, the rapidity of arterial occlusion, the presence of cerebrovascular collateral circulation, the metabolic state of brain tissue, patient’s age and medical comorbidities. Generally, the acute phase of stroke is the first 48 h after stroke symptom onset, the subacute phase of stroke is the period between 48 h to 6 weeks, to 3 or 6 months post-stroke, whereas the chronic phase starts 3 to 6 months after stroke (Bernheisel et al, 2011; Donnan et al, 2008; Kang et al, 2004; Maraka et al, 2014; Parsons et al, 2000; Poh, 2013; van Delden et al, 2012). …”
Section: Introductive Remarks: the Importance Of Enhancing Stroke Recmentioning
confidence: 99%